Tangible programming and informal science learning: making TUIs work for museums. - Horn, Michael S.; Solovey, Erin Treacy.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
In this paper we describe the design and initial evaluation of a tangible computer programming exhibit for children on display at the Boston Museum of Science. We also discuss five design considerations for tangible interfaces in science museums that guided our development and evaluation. In doing so, we propose the notion of passive tangible interfaces. Passive tangibles serve as a way to address practical issues involving tangible interaction in public settings and as a design strategy to promote reflective thinking. Results from our evaluation indicate that passive tangibles can preserve many of the benefits of tangible interaction for informal science learning while remaining cost-effective and reliable.